Nexus Between Environmental Innovation, Energy Efficiency, and Environmental Sustainability in G7: What is the Role of Institutional Quality? - JinRu, Long; Qamruzzaman, Md (Frontiers in Environmental Science, 2022)
The motivation of this study is to evaluate the role of environmental innovation, energy efficiency, and institutional quality in achieving sustainable environmental improvement in the G7 economy for the period 1980–2020. The study has implemented several econometrical tools for gauging their empirical association, including cross-sectional autoregressive distributed lag (ARDL) and directional causality with Dumitrescu-Hurlin. Study findings with cross-sectionally dependency test revealed that variables are sharing common dynamics, while the panel test of stationary documented all the variables were stationary after the first difference. Furthermore, the panel counteraction test established a long-run association among research variables. The variables coefficients with CS-ARDL revealed that renewable energy integration and environmental innovation expedite the scope of sustainability in the G7 economy in the long run. Furthermore, institutional quality assists in augmenting the process of ecological balance, that is, efficient institutional presence inductees affecting environmental policies implementation. Directional causality documented feedback hypothesis between renewable energy and environmental sustainability, environmental innovation and environmental sustainability. Moreover, the unidirectional causality was revealed between institutional quality and environmental sustainability. By considering the findings, a study has advocated that considerable time and efforts have to invest in formulating environmental policies to encourage clean energy integration for ensuring environmental quality and promoting environmental innovation.